DEVELOPMENT OF SOCIAL NETWORKS AND SERVICES IN TEACHING STUDENTS: EXPERIENCE OF DISTANCE LEARNING IN THE CONTEXT OF THE COVID-19 PANDEMIC - Kuznetsova, Elena; Dianov, Dmitry; Polozhentseva, Irina; Lobazova (Revista Inclusiones, 2020)
The pandemic caused by the acute respiratory disease COVID-19 has forced the education system to switch to distance learning, either partially or completely. The use of social networks can bring greater interactivity into the educational process under these conditions, have a positive effect on the results of students’ cognitive activity, and become an efficient means of increasing the motivation and quality of learning, organizing the collective work of students, performing joint project activities, and individualizing the student’s virtual learning space. Social networks can also be used as a means of distributing educational material. The specifics of the applications and the capabilities of social networks and services in distance learning have been described in the article; a theoretical analysis of the basic concepts of the articulated topic of the article has been carried out. Learning tasks have been identified on the basis of an expert survey, which can be solved through social networks; the applications of social networks VKontakte and Facebook for organizing distance educational process have been described; and methods of combining social networks and an information and organizational distance learning environment have been presented.